Pengendalian Nematoda Puru Akar (Meloidogyne spp.) Pada Seledri Dengan Bokashi Kipahit Dan Trichoderma sp. - Baihaki, Baihaki; Liestiany, Elly; Salamiah, Salamiah (www.ulm.ac.id, 2024)
The celery plant (Apium graveolens L.) is a cultivated leaf vegetable that has advanced capabilities and has a high selling value. Celery also has many properties which are commonly used as decoration and flavoring in cooking. One of the obstacles in increasing celery production is nematode attacks. Nematodes (Meloidogyne spp.) which can affect the number of leaf stalks. The aim of this research was to determine the ability of Bokashi kipahit Plus Trichoderma sp. to reduce attacks by root knot nematodes (Meloidogyne spp.) on celery plants (Apium graveolens L.). The research was designed using a Completely Randomized Design (CRD). What was studied was the impact of giving Bokashi kipahit, Trichoderma sp. and Bokashi kipahit plus Trichoderma sp. The research consisted of four treatments and four replications. The results of the research showed that giving Bokashi kipahit 15.5g/polybag added with Trichoderma sp. 20g/polybag can reduce the NPA population by 48%, and can increase the number of celery stalks by 39%.